Synergetic Effect of Macroeconomic Determinants on Stressed Assets of Indian PSU Banks: An analysis of the impact of macroeconomic determinants on stressed assets of Indian PSU banks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian banking system is under threat of continuous deterioration in asset quality. The problem is more serious in PSU banks. The level of stressed assets popularly known as NPA has drastically increased in public sector banks in the recent past. There are various macroeconomic and microeconomic indicators which render impact on NPA of banks. The problem is serious and growing rapidly with a distressing rate. An attempt has been made in the present study to examine the multiparty impact of selected variables on NPA. Macroeconomic indicators viz. GDP, Interest rates, Inflation and Exchange rate together had greater impact on NPA of PSU banks. During the study period level of Gross and Net NPA has shown various movements which has been expressed through bar diagrams. Study focuses on determining combined impact of selected variables on NPA and various movements during study period in NPA of PSU banks in India.